THE USE OF BUILD-A-SENTENCE CUBES GAME IN TEACHING SIMPLE PAST TENSE - Anugerah, Rezza; Wijaya, Bambang; Bunau, Eusabinus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstract: The purpose of this research was to know the effectiveness of using Build-A-Sentence Cubes Game in teaching simple past tense. This research was conducted through A-Pre experimental design. The subject of this research was the Eighth Level students of Q-Learning Course Pontianak in academic year 2014/2015 which consisted of 16 students. The technique of the data collecting was measurement technique by administering the written test in form of multiple choices which consists of thirty items. Then, the data were analyzed by effect size formula. The result of the post test revealed that the mean score was 73.2 while their mean score in pre-test was 60.7. The computation of the effect size with the score 0.94 (0.50 to 0.79) showed that the treatment or the use of Build-A-Sentence Cubes Game has the moderate effect in teaching simple past tense to the Eighth Level students of Q-Learning Course Pontianak in academic year 2014/2015. The alternative hypothesis was accepted and the effect of the treatment was categorized as moderate effect. Keywords: Build-A-Sentence Cubes, Simple Past Tense Abstrak: Tujuan dari penelitian ini adalah untuk mengetahui efektivitas penggunaan permainan Build-A-Sentence Cubes dalam mengajar simple past tense. Penelitian ini dilakukan dengan bentuk Pre-eksperimental. Subjek penelitian ini adalah siswa level 8 Q-Learning Course Pontianak pada tahun akademik 2014/2015 yang terdiri dari 16 siswa. Teknik pengumpulan data dilakukan menggunakan teknik pengukuran dengan pemberian tes tertulis berupa pilihan ganda yang terdiri dari tiga puluh item. Kemudian, data dianalisis dengan rumus ukuran efek. Hasil post test mengungkapkan bahwa skor rata-rata adalah 73,2 sedangkan skor rata-rata mereka dalam pre-test adalah 60,7. Perhitungan ukuran efek dengan skor 0,94 (0,50-0,79) menunjukkan bahwa penggunaan permainan Build-A-Sentence Cubes memiliki efek moderat dalam mengajar simple past tense kepada siswa Level 8 Q-Learning Course Pontianak pada tahun akademik 2014/2015. Hipotesis alternatif diterima dan efek dari treatment dikategorikan sebagai efek moderat. Kata Kunci: Build-A-Sentence Cubes, Simple Past Tense